The growth performance and costs of rearing friesian crossbreed dairy young stock in Malaysian commercial farm - Ang, Xin Tong; Mohd Nor, Norhariani; Sithambaram, Shanmugavelu; Mark, Wen Han Hiew; Khairuddin, Uswah; Shapiai, Mohd Ibrahim; Mohd Suhaimi, Nurul Aisyah; Peter, Lee Ah Kong; Hanapiah, Muhammad Ali (Institut Pertanian Bogor, Bogor Agricultural University, 2021)
The important elements in rearing dairy young stock are good farm management, proper growth and optimal costs of rearing. A survey on these important elements was conducted at two commercial farms in Johor and Sabah in 2019. The farm herd size is 214 heads and 2,221 heads with 163,682 litres and 4.2 mil. litres of milk production, in Johor and Sabah respectively. In addition, the body weight data of 188 dairy young stock was collected and analysed to determine the growth performance using polynomial growth function. The results showed the two farms have young stock with different Friesian blood levels (60% and 70% in Johor, and 87.5% in Sabah) with different growth performance. The average weight of dairy young stock with 60%, 70% and 87.5% Friesian blood levels at birth were 21.31±3.70kg, 22.33±2.23kg and 26.55±2.68kg, respectively, while average weight at 3 months of age were 45.00±7.07kg, 55.57±8.36kg and 75.84±12.54kg, respectively. Heifers with 87.5% Friesian blood levels was bred at 15 months of age (444kg) while heifers with lower Friesian blood levels was bred 6 months later (250kg). The average rearing (feed) cost was RM4,932 (USD1,194)/heifer. The findings of this study can give awareness and insights in the performance and costs of rearing crossbreed dairy young stock in tropics.